Intrapartum fetal heart rate monitoring in cases of cytomegalovirus infection - Kaneko, Masatoki; Sameshima, Hiroshi; Ikeda, Tomoaki; Ikenoue, Tsuyomu; Minematsu, Toshio (American journal of obstetrics and gynecology, 2004)
Several studies have shown that abnormal intrapartum fetal heart rate patterns are the results from pre-existing fetal brain damage. We evaluated intrapartum fetal heart rate pattern of cytomegalovirus-infected fetuses and correlated the patterns with neurologic outcomes. Between 1991 and 2001, there were 20 cytomegalovirus-infected fetuses. We selected 40 fetuses as control subjects that were matched for gestational age and birth weight. Fetal heart rate was interpreted according to the guidelines of the National Institute for Child and Human Development. The incidence of abnormal fetal heart rate pattern and umbilical blood gases were compared between both groups. We also investigated the factors that contributed to abnormal fetal heart rate pattern in the cytomegalovirus group. Nonreassuring fetal heart rate patterns (prolonged deceleration and recurrent late deceleration) were observed in 8 of 20 fetuses (prolonged deceleration, 7 fetuses; recurrent late deceleration, 1 fetus) in the cytomegalovirus group and in 3 of 41 fetuses (prolonged deceleration, 1 fetus; recurrent late deceleration, 2 fetuses) in the control group (P<.05, Fisher test). Baseline fetal heart rate variability was minimal in 4 of the 7 prolonged deceleration cases in the cytomegalovirus group. Umbilical pH <7.1 was found for 1 fetus in the cytomegalovirus group. The average umbilical arterial pH values were similar in both the groups. In the cytomegalovirus group, there were no differences in the incidence of contributing factors between 8 fetuses with abnormal fetal heart rate pattern (prolonged deceleration and recurrent late deceleration) and 8 fetuses with no change. There were 3 fetuses with cerebral palsy: 2 fetuses in the no change group and 1 fetus in the prolonged deceleration group. Antigenemia was positive exclusively in 4 cases with abnormal fetal heart rate pattern (P<.05). Cytomegalovirus-infected fetuses are more likely to show abnormal intrapartum fetal heart rate patterns than low-risk control fetuses, which suggests that the perinatal detection of cytomegalovirus is necessary to distinguish hypoxic-ischemic encephalopathy.